Violence Against Women - Johnson, Holly (Springer, 2017)
The International Violence against Women Survey (IVAWS) has interviewed over 23,000 women in eleven countries (including Australia, Costa Rica, the Czech Republic, Denmark, Greece, Hong Kong, Italy, Mozambique, the Philippines, Poland and Switzerland) about their experiences with gender-based violence. Violence against Women: An International Perspective presents the comparative results for nine of these countries, testing current theories about male violence against women, and offering both global context and implications for other areas of the world. Included are findings on: Prevalence and severity. Risk factors and correlates. Physical and psychological consequences Percentage of violent incidents reported to police and other agencies. Criminal justice system response and women’s assessment of these Plus charts, tables, and the IVAWS questionnaire. These data are vital to researchers, advocates, and policymakers working to assist survivors and eliminate gender-based violence worldwide. In addition, the authors offer immediate and long-range proposals, from promoting gender equality and improving service delivery to victims to improved prevention, monitoring and evaluation.